(untitled) (International Journal of Management and Sustainability, 2014)
Stock market is a place where the securities of listed companies are traded and this can be affected by both macroeconomic and non-macroeconomic factors. The impacts of macroeconomic factors on stock market of Pakistan are investigated in the current study. For this purpose monthly data covering the period from January 2008 to December 2012 is used in this study while taking the three most important macroeconomic variables, Exchange Rate, Interest Rate and Inflation. Using the more advance Bound Testing Approach, a very strong long run cointegration is found amongst the variables taken for the study. In the long span of time, the results suggest that both Exchange Rate and Interest Rate have negative association with stock market of Pakistan while the Inflation Rate does not create such a condition that affect the stock market of Pakistan. Same results are found for the shorter version of time.